In-Vitro Antioxidant, Antihyperlipidemic, and Antihypertensive Activities of Ethanol Extract of Pedada Stem Bark (Sonneratia caseolaris L.) - Haryoto, Haryoto; Raharjo, Danang (Urecol Journal. Part C: Health Sciences, 2025)
Pedada (Sonneratia caseolaris) is one type of mangrove from the genus Sonneratia with high flavonoid content that has the potential as an antioxidant. Flavonoids as antioxidants can improve blood lipid profiles by lowering total cholesterol, triglycerides, and LDL, and increasing HDL. In addition, flavonoids can inhibit the activity of Angiotensin-converting enzyme (ACE) so that it has the potential as an antihypertensive. This study aims to examine the potential of kedabu leaf extract as an antioxidant, antihypertensive and antihyperlipidemia agent tested in vitro. Antioxidant testing was carried out using the ABTS (2,2-azinobis-3-ethylbenzothiazoline-6sulfonate) method, antihypertensive testing was carried out by inhibiting Angiotensin converting enzyme and antihyperlipidemia was carried out by inhibiting the lipase enzyme. The results of the study showed that the total flavonoid content was 24.827 ± 0.327 mgQE / g mgQE / g with an antioxidant capacity with an IC50 value of 54.166 ± 0.558 ppm. From the Angiotensin converting enzyme inhibition test and lipase enzyme inhibition, the IC50 values ??were 33.843±0.157 ppm and 63.709±0.819 ppm, respectively. Based on these results, the pedada bark extract showed antihypertensive and antihyperlipidemic activity by inhibiting the activity of Angiotensin converting enzyme and lipase enzyme.